Perencanaan Desain Sekolah Luar Biasa (SLB) Bina Karya Insani Dengan Konsep Green Design - Dian Wibawa, Putri; Kristiana Seftianingsih, Dina; Syahnas Paradita, Dea (JURNAL ASSOSIATIV, 2025)
The planning of the Bina Karya Insani Special School (SLB) with the Green Design concept aims to improve comfort for children with disabilities. This study focuses on the application of environmentally friendly design principles including the use of sustainable materials, energy efficiency, and optimization of lighting and natural ventilation. The method used design thinking that focuses on innovation in solving user-centered problems. This method combines elements of designer intuition, logical processes, and systematic reasoning to create creative and effective solutions. The results indicate that the application of the Green Design concept in the planning of the Bina Karya Insani Special School can provide a healthier and more comfortable learning environment for children with disabilities. Environmentally friendly materials and natural lighting systems not only support physical health but also the psychological well-being of students. In addition, energy efficiency contributes to reducing school operational costs. Thus, the planning of the SLB based on Green Design not only optimally supports the special needs of children but also creates a sustainable and energy-efficient environment. This study is expected to be a reference for the planning and construction of other educational facilities that are environmentally friendly and inclusive. Keywords : SLB, Green Design, Children with Disabilities, Design Thinking.